Vulnerability to HIV among older men who have sex with men users of dating apps in Brazil - Queiroz,Artur Acelino Francisco L.N. (2019)
ABSTRACT Introduction: The elderly population is increasingly benefiting from recent technological advances. In this scenario, geolocation-based dating applications provide a viable alternative for finding partners in a practical and timely manner, but may be accompanied by certain risk behaviors for HIV infection. Although there are considerable number of users over 50 on these applications, no studies have addressed this problem. The aim of the present study was to analyze factors of vulnerability to HIV/Aids among the population of men who have sex with men (MSM) age 50 years or older who use dating apps. Methods: This was a cross-sectional, population-survey-based, analytical study, conducted exclusively online with a sample of 412 MSM. The data was collected from the following apps: Grindr®, Hornet®, Scruff® and Daddy Hunter®. Results: Factors associated with a higher chance of having HIV were: sexual relations with an HIV-infected partner (ORa = 5.53; 95%CI = 2.23-13.73); chemsex (ORa = 3.97; 95%CI = 1.72-8.92); and, above all, having an HIV-infected partner (ORa = 8.02; 95%CI = 2.01-32.01). The belief that apps increase protection against sexually transmitted infections (ORa = 0.43; 95%CI = 0.19-0.95) and not being familiar with post-exposure prophylaxis (ORa = 0.43; 95%CI = 0.19-0.95) were associated with decreased chances of having HIV. Conclusions: We highlight some important factors that structure the vulnerability of the MSM surveyed in relation to HIV infection. The findings should be used to customize care for this population, which could bring them in more for health care services.